Violation of the right to electronic privacy in public international law - Ahmed Medan, Salwa (Opción, 2020)
Because of the abundance of the violation of privacy and the absence of the individuals awareness regarding its risks and the weakness of the national and international observation on the electronic environment in general and the platforms of communication specifically, we are obliged to seek about these violations in terms of their images, risk, the activation of the legal national rules and the technical techniques in deterring or reducing them. At the end of our research, we reached too many conclusions and proposals that we hope they will be taken to eliminate this phenomenon.